Co-infection with SARS-CoV-2 and Influenza A Virus in Patient with Pneumonia, China - Wu, Xiaojing; Cai, Ying; Huang, Xu; Yu, Xin; Zhao, Li; Wang, Fan; Li, Quanguo; Gu, Sichao; Xu, Teng; Li, Yongjun; Lu, Binghuai; Zhan, Qingyuan (Emerging infectious diseases, 2020)
We report co-infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and influenza A virus in a patient with pneumonia in China. The case highlights possible co-detection of known respiratory viruses. We noted low sensitivity of upper respiratory specimens for SARS-CoV-2, which could further complicate recognition of the full extent of disease.